Power losses test for electrical machine design on non-grain oriented different thickness material - Md. Reza, Mohyin; Ismail, Daut, Prof. Dr.; Nor Ashbahani, Md. Kajaan (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/